2019
DOI: 10.1155/2019/6534745
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic View Exploring the Role of Chloroplasts in Plant Abiotic Stress Responses

Abstract: Chloroplasts are intracellular semiautonomous organelles central to photosynthesis and are essential for plant growth and yield. The significance of the function of chloroplast-related genes in response to climate change has not been well studied in crops. In the present study, the initial focus was on genes that were predicted to be located in the chloroplast genome in rice, a model crop plant, with genes either preferentially expressed in the leaf or ubiquitously expressed in all organs. The characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Research has revealed a close association between the chloroplast-related genes and high-temperature stress in the model plant rice. The expression of more than two hundred genes was upregulated in response to heat stress [49]. In a series of plant Retrograde signaling pathways refer to the communications from the plastid to the nucleus [13].…”
Section: Response To Heat Stressmentioning
confidence: 99%
“…Research has revealed a close association between the chloroplast-related genes and high-temperature stress in the model plant rice. The expression of more than two hundred genes was upregulated in response to heat stress [49]. In a series of plant Retrograde signaling pathways refer to the communications from the plastid to the nucleus [13].…”
Section: Response To Heat Stressmentioning
confidence: 99%
“…We retrieved GO terms related to the biological process from the rice oligonucleotide array database (http://ricephylogenomics-khu.org/ROAD_old/analysis/go_enrichment.shtml, temporary page for updating) [100]. To carry out enrichment analysis, we applied threshold query number of >2, hyper p-value < 0.05, and fold enrichment value (query number/query expected number) >2, as previously reported [101,102]. The enriched GO terms were visualized using R studio software and ggplot2 R package (R studio version: 1.1.453, ggplot2 version: 3.0.0).…”
Section: Rna-seq and Analysismentioning
confidence: 99%
“…The metabolites synthesized in chloroplasts protect plants from abiotic and biotic stresses, including heat, cold, drought, salt, light, and pathogens [ 346 , 347 ]. Through meta-expression analyses under abiotic stress conditions, Yoo et al [ 348 ] identified 264 cold or heat stress-responsive plastid-related genes in rice. Furthermore, the functional characterization of plastid-related genes emphasized the significance of genes for crosstalk between chloroplast development and heat stress.…”
Section: Explored Mechanisms Of Abiotic Stress Tolerance For Crop Improvementmentioning
confidence: 99%